Molecular Characterization of Magnesium Chelatase in Soybean [Glycine max (L.) Merr.] - Zhang, Dan; Chang, Enjie; Yu, Xiaoxia; Chen, Yonghuan; Yang, Qinshuai; Cao, Yanting; Li, Xiukun; Wang, Yuhua; Fu, Aigen; Xu, Min (Frontiers in Plant Science, 2018)
Soybean (Glycine max) seed yields rely on the efficiency of photosynthesis, which is poorly understood in soybean. Chlorophyll, the major light harvesting pigment, is crucial for chloroplast biogenesis and photosynthesis. Magnesium chelatase catalyzes the insertion of Mg2+ into protoporphyrin IX in the first committed and key regulatory step of chlorophyll biosynthesis. It consists of three types of subunits, ChlI, ChlD, and ChlH. To gain a better knowledge of chlorophyll biosynthesis in soybean, we analyzed soybean Mg-chelatase subunits and their encoding genes. Soybean genome harbors 4 GmChlI genes, 2 GmChlD genes, and 3 GmChlH genes, likely evolved from two rounds of gene duplication events. The qRT-PCR analysis revealed that GmChlI, GmChlD, and GmChlH genes predominantly expressed in photosynthetic tissues, but the expression levels among paralogs are different. In silicon promoter analyses revealed these genes harbor different cis-regulatory elements in their promoter regions, suggesting they could differentially respond to various environmental and developmental signals. Subcellular localization analyses illustrated that GmChlI, GmChlD, and GmChlH isoforms are all localized in chloroplast, consistent with their functions. Yeast two hybrid and bimolecular fluorescence complementation (BiFC) assays showed each isoform has a potential to be assembled into the Mg-chelatase holocomplex. We expressed each GmChlI, GmChlD, and GmChlH isoform in Arabidopsis corresponding mutants, and results showed that 4 GmChlI and 2 GmChlD isoforms and GmChlH1 could rescue the severe phenotype of Arabidopsis mutants, indicating that they maintain normal biochemical functions in vivo. However, GmChlH2 and GmChlH3 could not completely rescue the chlorotic phenotype of Arabidopsis gun5-2 mutant, suggesting that the functions of these two proteins could be different from GmChlH1. Considering the differences shown on primary sequences, biochemical functions, and gene expression profiles, we conclude that the paralogs of each soybean Mg-chelatase subunit have diverged more or less during evolution. Soybean could have developed a complex regulatory mechanism to control chlorophyll content to adapt to different developmental and environmental situations.